The use of transpulmonary contrast echocardiography – a first experience in Serbia - Stojšić-Milosavljević, Anastazija; Ilić, Aleksandra; Stojšić, Snežana; Ivanović, Vladimir; Milićević, Jelena; Kovač, Robert; Stefanović, Maja; Tadić, Snežana; Miljković, Tatjana; Bjelobrk, Marija; Dabović, Dragana; Živkov-Šaponja, Dragoslava; et al. (Vojnosanitetski pregled, 2021)
Background/Aim. Contrast echocardiography (CE) is an echocardiographic modality where ultrasound contrast echocardiographic agent (CEA) is introduced peripherally for the image enhancement. The aim of this study was to present the initial clinical experience of the use of CEA Optison™ (GE Healthcare, Princeton, NJ) at the Institute for Cardiovascular Diseases of Vojvodina, Serbia and prospectively monitor the occurrence of possible side effects. Methods. A total of 357 patients were referred for resting or stress echocardiographic examinations, with an approved indication for CEA administration. The average age of patients was 63.3 years (range, 21–92 years), 62% of them were men. Most of the patients (77.31%) had some form of ischemic heart diseases. Hypertension was the most frequent risk factor (77.03%), but 57 patients had diabetes mellitus and 33 patients had chronic kidney disease as comorbidity. Most (90.5%) of the patients were on beta blocker therapy, 83.5% of them on angiotensin converting enzyme/angiotensin receptor blockers. Majority (80.3%) of the patients received single or dual (49.5%) antiagregation therapy, 74 (26.3%), of them were on anticoagulation therapy, 55.1% of the patients were taking diuretics. The global ejection fraction (EF) was preserved in 39.85% of them, the majority (136 of them), had left ventricle (LV) impairment, with an EF less than 50%. Patients were followed up for 30 minutes after CEA administration for potential side effects. In 118 patients, vital signs (heart rate, oxygen saturation, body temperature, systolic and diastolic blood pressure) were measured before and 30 minutes after CEA administration. Results. The administration of CEA was not associated with side effects. Diastolic blood pressure drop and heart rate increase were statistically, but not clinically significant (p = 0.027 and p = 0.028, respectively). Conclusion. Changes in analyzed vital signs were clinically non relevant. CE is a safe noninvasive diagnostic modality for patients undergoing rest and stress echocardiography.